Meningkatkan Kerja Sama Peserta Didik Menggunakan LKPD Kolaboratif Melalui Layanan Bimbingan Klasikal - Dimas Arya Figuna; Vivi Rahmawati; Nining Solekah (CV. ITTC INDONESIA, 2025)
Collaboration is an essential skill for students, especially in completing group tasks. Observations in class VII D at SMPN 4 Kediri revealed a lack of collaborative attitude, participation, and communication among students during discussions. This study aims to enhance students' collaborative attitudes in the learning process, particularly when working on group assignments. The activities were conducted through classical guidance services utilizing collaborative LKPD media. The research was carried out in two cycles with a total of three meetings, starting from the pre-cycle, followed by cycle I and cycle II. Each cycle consists of four stages: planning, implementation, observation, and reflection. The subjects of the study were 32 students from class VII D. The results showed a significant improvement in collaborative attitudes, with an average of 36% in the pre-cycle, increasing to 41% in cycle I, and reaching 51% in cycle II. This indicates the effectiveness of collaborative LKPD in enhancing student cooperation.